SALT CRYSTALLIZATION IN PORES: QUANTIFICATION AND ESTIMATION OF DAMAGE - Angeli M.; Bigas J.; Benavente D.; Menéndez B.; Hébert R.; David Ch. (My University, 2007)
The objective of this study is to understand and predict the alteration of porous rock by crystallization of salts. Samples of different rocks have been tested according to the EN 12370 standard test. Two parameters are proposed to evaluate the alteration of a rock during these tests. The alteration index AI represents the cycle in which the first damages occur. The alteration velocity AV represents the alteration rate at the end of the experiment, when the decay has become regular. These parameters can be estimated with the help of a microstructural study of the rocks. The most relevant intrinsic parameters of the stones for this estimation are capillary coefficient, evaporation coefficient, tensile strength and P-waves velocity. An evaluation of the alteration pattern is also proposed depending on the eventual heterogeneities and anisotropies of the rocks. The influence of the dimension and shape of the samples is also discussed.
Keywords: SALT CRYSTALLIZATION; ALTERATION; QUANTIFICATION; ESTIMATION; EVAPORATION; DURABILITY